Subluminal Evolution and Superluminal Creation of Dark Energy (Global Journal of Science Frontier Research, 2016)
In an attempt to find an origin of dark energy it is found that the hypothetical pair of gravitationally bound Planckeon of mass m pl ~ 0.5g and the Higgs boson of masss m H ~ !0 -4 m pl creates a negative attractive potential -Gm pl m H /l pl . The corresponding temperature of thermal creation T ~ 10 28 K is higher than T ~10 27 K accepted by the standard inflationay cosmology, but within the asymptotic limit T ~ ∞ interpolated from Hubble's expansion history to the point origin of the Hubble universe.
Keywords: hypothetical pair; inflationay cosmology; gravitationally